Kajian Peran Yeast dalam Pembuatan Tempe - Maria Erna Kustyawati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
While filamentous fungi R. oligosporus was the main microorganism in the tempe production, the growth of bacteria was found to take a role in the tempe fermentation and yeasts might have an important contribution to the improvement of the tempe quality. In this study four yeasts of extracellular enzymatic producer, of which: Saccharomyces boulardii, Yarrowia lipolytica, Geotrichum candidum, and Aerobasidium pullulans were inoculated individually with the mold Rhizopus oligosporus into soybeans fermentation for tempe production. The growth of microorganisms including the colony forming unit of bacteria, yeasts, and fungi were analyzed on cultural plates at the fermentation time of 0, 12,24, 36, and 48 h. The result showed that S. boulardii, Y. lipolytica, G. candidum, were grown with natural bacteria dan R. oligosporus to the population of 107, 108, 109 cfu/g, respectively, bacteria was grown up to 109-1010cfu/g as expected. Folic acid contents (μg/100g) of tempe inoculated with R.oligosporus only, and with addition of S.boulardii, G.candidum, and Y.lipolytica were 72,76; 89,28; 62,45; 19,62 respectively. Daidzein contents (%) were 0,77; 0,78; 0,76; 0,67, respectively. Vitamin B contents were 3,79; 3,95;3,76; 3,92, respectively.ABSTRAKWalaupun Rhizopus oligosporus sebagai kapang utama dalam pembuatan tempe, ternyata bakteri mempunyai fungsi yang sangat penting selama fermentasi tempe, dan diduga yeast juga mempunyai peran dalam pembuatan tempe. Dalam penelitian ini empat jenis yeast (Saccharomyces boulardii, Yarrowia lipolytica, Geotrichum candidum, dan Aerobasidium pullulans) yang diketahui sebagai penghasil enzim ekstraseluler lipolitik dan proteolitik digunakan se- bagai inokulum bersama dengan R. oligosporus dalam fermentasi kedelai untuk pembuatan tempe. Masing masing ye- ast diinokulasikan secara terpisah bersama dengan R. oligosporus. Pertumbuhan mikroorganisme selama fermentasi diikuti dengan melihat unit pembentuk koloni (CFU) dari bakteri, yeast, dan kapang dilakukan pada saat preinkubasi kedelai yang telah diinokulasi dan pada lama fermentasi 0 jam, 12 jam, 24 jam, 36 jam dan 48 jam.Hasilnya bahwa S. boulardii, G. candidum, dan Y. lipolytica, mampu tumbuh bersama bakteri alami tempe dan R. oligosporus sampai pada populasi masing-masing 107, 108, 109 cfu/g, pertumbuhan bakteri sampai 109-1010cfu/g. Kandungan asam folat (μg/100g ) dalam tempe dengan R. oligosporus saja dan penambahan dengan S. boulardii, G. candidum, Y. lipolytica adalah berturut-turut 72,76; 89,28; 62,45; 19,62. Kandungan daidzein (%) adalah 0,77; 0,78; 0,76; 0,67. Kandungan vit B (mcg/100g) adalah 3,79; 3,95;3,76; 3,92.